The Future of Telehealth in Allergy and Immunology Training - Keswani, Anjeni (J Allergy Clin Immunol Pract, 2020)
With emerging interest in the use of telemedicine, allergy-immunology should be at the forefront of adoption and implementation of these services. Patients report a greater desire for telemedicine services as well as satisfaction with video-based visits with their providers. Interim virtual visits can accommodate overscheduled clinics, reduce burdens of travel to distant sites, improve access to subspecialty care, and increase adherence during monitoring of chronic allergic conditions. The outpatient nature of allergy-immunology coupled with the ease of conducting many aspects of a routine visit via telemedicine makes the incorporation of telehealth training into fellowship programs highly desirable. The short-term closure of hospital-affiliated clinics, in particular, for vulnerable or immunodeficient patients, in the setting of a global pandemic demonstrates the timeliness of this topic. A framework for implementing telemedicine into the allergy-immunology curriculum, training faculty on appropriate supervision, providing elective clinical experience in the form of continuity clinics, and simulating telemedicine delivery is discussed. Proposed telemedicine competencies desired for the independent practice of telemedicine are suggested.